2018
DOI: 10.1111/tbed.12801
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to West Nile virus and tick-borne encephalitis virus in dogs in Spain

Abstract: In the past decade, the spread of emerging zoonotic flaviviruses (genus Flavivirus, family Flaviviridae) has been reported in many regions worldwide, representing a threat to both human and animal health. A serosurvey was carried out to assess exposure and risk factors associated with antigenically related flaviviruses, particularly West Nile virus (WNV), Usutu virus (USUV) and tick-borne encephalitis virus (TBEV), in dogs in Spain. Flavivirus antibodies were detected in 39 of 815 dogs (4.8%; 95% CI: 3.3-6.3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Among the seropositive animals by cELISA, the confirmatory rate by MNT and MIA was higher and the mean % S/N of cELISA was lower for wild boar, suggesting higher antibody titrer in wild boar. Similar differences in the seroprevalence of flavivirus infections (as regards WNV) were found between wild boar and cervids (roe deer and red deer) in Spain [28,31,35]. These results may suggest lower antibody response in roe deer to infections by flaviviruses of the Japanese encephalitis antigenic complex.…”
Section: Spatiotemporal Circulation Of Usuv In Francesupporting
confidence: 58%
See 2 more Smart Citations
“…Among the seropositive animals by cELISA, the confirmatory rate by MNT and MIA was higher and the mean % S/N of cELISA was lower for wild boar, suggesting higher antibody titrer in wild boar. Similar differences in the seroprevalence of flavivirus infections (as regards WNV) were found between wild boar and cervids (roe deer and red deer) in Spain [28,31,35]. These results may suggest lower antibody response in roe deer to infections by flaviviruses of the Japanese encephalitis antigenic complex.…”
Section: Spatiotemporal Circulation Of Usuv In Francesupporting
confidence: 58%
“…TBEV/LIV seropositivity in Hautes-Pyrénées could originate from an infection with LIV or LI-like virus, since these viruses have been reported in sheep, goats and Cantabrian chamois (Rupicapra pyrenaica parva) in close geographical areas in Spain: In the Basque and Asturias regions [23,25,63]. The presence of a virus from the TBEV-serocomplex was found at a broader scale in Spain by serology, with antibodies neutralizing TBEV reported in southern Spain and on the island of Mallorca [28,29]. The positive serum in the Yvelines might also reveal the western limit of distribution of TBEV in France.…”
Section: Tbev Serocomplex Distributionmentioning
confidence: 94%
See 1 more Smart Citation
“…This study supports previous studies, which identified horses and dogs as suitable sentinel species for WNV [53,54]. WNV seroprevalence in dogs (6.3%) and horses (3.1%) was similar to conventional sampling of the species in different areas with WNV activity [67][68][69]. Nevertheless, the seroprevalence in horses was markedly lower than in southeastern Romania (15.1%) [70].…”
Section: Discussionsupporting
confidence: 88%
“…Several IgG tests for equine and human TBEV and WNV infections are available, but the observed cross‐reacting antibodies often lead to false‐positive results (Beck et al, ; Cleton et al, ; Sanchini et al, ; Ziegler et al, ). This is of concern especially in areas of co‐circulation of two or more flaviviruses (García‐Bocanegra et al, ). Whereas TBEV is known since decades to be endemic in many parts of Europe, WNV has emerged more recently (Bakonyi et al, ; Barzon, ) and its activity has dramatically increased during the last decade, with large outbreaks in humans and horses reported each year (Bakonyi et al, ).…”
Section: Discussionmentioning
confidence: 99%